Strengthening character education in fostering a wise attitude using social media - Ninies Eryadini (PPPM STKIP PGRI Lamongan, 2021)
Today's rapidly developing technological advances, not only bring convenience and comfort to people but also contribute to many worrying problems. The development of social media with the ins and outs of a virtual world that is free without limits will have a negative impact if it is not used wisely. The existence of technological developments that make it easier to access social media should have a positive impact and bring benefits, especially for students, but it is often misused so that it has negative impacts and problems that ultimately weaken the character of the nation's children. . Therefore, strengthening character education is an important thing to do. The values ​​of religious character, nationalism, independence, integrity, and gotong royong do not stand and develop alone, but interact and develop dynamically to form personal integrity. Armed with a good character, an individual will be better at speaking and communicating through social media. Individuals who have a strong character will be wiser in using social media.